A New Method for Intramolecular Chloroamination of Unfunctionalized Olefins. Issue 2 (25th January 2013) - Liu, Gong‐Qing; Li, Wei; Li, Yue‐Ming
Abstract A new method for the intramolecular chloroamination of unfunctionalized olefins is reported. The reactions were carried out at room temperature for 3 h using hydrated copper(II) chloride as both promoter and chlorine source, and the corresponding vincinal haloamines were obtained in good isolated yields.